Effectiveness of Vildagliptin in Clinical Practice: Pooled Analysis of Three Korean Observational Studies (the VICTORY Study) - Sunghwan Suh; Sun Ok Song; Jae Hyeon Kim; Hyungjin Cho; Woo Je Lee; Byung-Wan Lee (Journal of Diabetes Research)
The present observational study aimed to evaluate the clinical effectiveness of vildagliptin with metformin in Korean patients with type 2 diabetes mellitus (T2DM). Data were pooled from the vildagliptin postmarketing survey (PMS), the vildagliptin/metformin fixed drug combination (DC) PMS, and a retrospective observational study of vildagliptin/metformin (fixed DC or free DC). The effectiveness endpoint was the proportion of patients who achieved a glycemic target (HbA1c) of ≤7.0% at 24 weeks. In total, 4303 patients were included in the analysis; of these, 2087 patients were eligible. The mean patient age was 56.99 ± 11.25 years. Overall, 58.94% patients achieved an HbA1c target of ≤7.0% at 24 weeks. The glycemic target achievement rate was significantly greater in patients with baseline HbA1c < 7.5% versus ≥7.5% (84.64% versus 43.97%), receiving care at the hospital versus clinic (67.95% versus 52.33%), and receiving vildagliptin/metformin fixed DC versus free DC (70.69% versus 55.42%). Multivariate logistic regression analysis indicated that disease duration (P<0.0001), baseline HbA1c (P<0.0001), and DC type (P=0.0103) had significant effects on drug effectiveness. Vildagliptin plus metformin appeared as an effective treatment option for patients with T2DM in clinical practice settings in Korea.